Role Congruity Theory and women’s perceptions of the challenges in achieving senior leadership roles: A descriptive focus group of a medium-sized Durban company 2018 - Mills, Amy (The IIE, 2018)
This research attempted to solve the problem of the perceived unequal treatment of women in the workplace. It described the Role Congruity Theory and how perceptions affect the challenges women face in achieving senior leadership roles. The problem is that there is a gender disparity in companies and this study discussed why. Inequality is fundamentally unjust, and companies and governments have an obligation to ensure that people are treated equally. The gap in knowledge was that, despite legislation, there is still perceived unequal treatment in South Africa and this study aimed to establish why. A focus group was conducted where women in senior leadership roles at one company discussed their experiences of perceived challenges they have faced. This was chosen because of the qualitative nature of the study and the interpretivist paradigm. The most significant findings from this study were that the perceived challenges of the women at the company studied were self-doubt and their own expectations of themselves. Contribution to the field of sociology was that these women did not see their gender as a challenge in the workplace of the company studied.
Keywords: Role Congruity Theory; women's perceptions; women in senior leadership; women's challenges; gender disparity